JURIDICAL ANALYSIS OF THE ROLE OF INVESTIGATORS IN RESOLVING CRIMINAL ACTS OF CHILD ABUSE THROUGH RESTORATIVE JUSTICE APPROACHES (RESEARCH STUDY AT THE COAL RESORT POLICE) - Taufiq Hidayat Thayeb; Cut Nurita; Tajuddin Noor (LPPM YPITI, 2025)
Restorative justice in persecution is an approach to criminal case resolution that involves perpetrators, victims, and related parties to find a common solution that emphasizes restoration rather than retaliation. The regulation of restorative justice law against children who commit criminal acts of abuse is based on Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, the Regulation of the National Police of the Republic of Indonesia Number 8 of 2021 concerning the Handling of Crimes Based on Restorative Justice. Law enforcement with restorative justice at the Batu Bara Resort Police in the process of investigating children as perpetrators of criminal acts of persecution is the application of an approach that prioritizes the recovery of victims and the community.